Cream-skimming, parking and other intended and unintended effects of performance-based contracting in social welfare services - Pierre Koning; Carolyn J. Heinrich (Institute for the Study of Labor (IZA), 2010)
In a growing number of countries, the delivery of social welfare services is contracted out to private providers, and increasingly, using performance-based contracts. Critics of performance-based incentive contracts stress their potential unintended effects, including cream-skimming and other gaming activities intended to raise measured performance outcomes. We analyze the incentive effects of performance-based contracts, as well as their impacts on provider job placement rates, using unique data on Dutch cohorts of unemployed and disabled workers that were assigned to private social welfare providers in 2002-2005. We take advantage of variation in contract design over this period, where procured contracts gradually moved from partial performance-contingent pay to contracts with 100%-performance contingent reward schemes, and analyze the impact of these changes using panel data that allow us to control for cohort types and to develop explicit measures of selection into the programs. We find evidence of cream-skimming and other gaming activities on the part of providers but little impact of these activities on job placement rates. Overall, moving to a system with contract payments fully contingent on performance appears to increase job placements for more readily employable workers, although it does not affect the duration of their jobs.
Keywords: I38; H11; H53; 330; Social welfare; performance contracting; Arbeitsvermittlung; Outsourcing; Personalberatung; Sozialer Dienst; Vertragsrecht; Leistungsanreiz; Arbeitslosigkeit; Niederlande